Evaluation of Polar Lipid Waste from Vegetable Oil Extraction: Insights from Experimental and Validated Simulation Results - Husodo, Amani Salsabil; Indah, Nindia Noor; Wardani, Ratri Puspita; Gunawan, Setiyo (Envirotek : Jurnal Ilmiah Teknik Lingkungan, 2025)
This paper examined the wastewater production attributed to the solvent-based cooking oil extraction using Aspen Plus simulation facilitated which has been confirmed by experimental results. Distillate condensates that had remaining solvents as well as free fatty acids (FFAs) were identified as waste streams. Three feedstocks were tested, Crude Nyamplung Oil (CNO), high-FFA Crude Palm Oil (CPO-acid), and regular Crude Palm Oil (CPO-regular). CNO generated 0.288 t/h of hexane and methanol traces of wastewater, whereas CPO-acid (1.338 t/h) and CPO-regular (1.419 t/h) contained ethanol. The stoichiometric oxidation was used to estimate chemical oxygen demand (COD), whereas FFA content was used to determine oil and grease (O&G). The COD values of untreated streams were 293.236 mg/L (CNO), 2511.39 mg/L (CPO-acid), and 1662 mg/L (CPO-regular), which were higher than the Indonesian standard (350 mg/L). Oil and Grease (O&G) values of the untreated waste streams were not met the standards. Solvent based processes are less polluting as compared to refinery effluents (COD >15000 mg/L, O&G 4000mg/L), yet not in compliance with COD. Solvency and FFA value to biodiesel or PFAD are suggested to be enhanced to decrease the environmental burden.